Science Concepts According to Syed Hussein Nasr - Hasan Bakti Nasution; Katimin Katimin; Salahuddin Harahap (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This Study aims to find out science concepts according Syed Hussein Nasr. The methodology of science in Islam is based on an epistemology that is fundamentally different from the epistemology that is dominant in modern Western science. For him, faith in the revelation of the Qur'an will reveal all the possibilities that exist in human reason. Submission to revelation, at every level makes sense capable of actualizing these possibilities. The development of Muslim reason is based on a complete awareness of this principle. In this perspective, in solving philosophical and scientific problems. Hence, it is understandable why purification of the soul is seen as an integral part of the methodology of knowledge. The purification of the soul is the main concern, for the protection and proper use of human reason. The religious and spiritual atmosphere created from the Koran at the same time removes obstacles to the development of a normal and optimal mind in the right way. Intellect here, is used in the sense of origin, intellectus (Latin) or nous (Greek).